SISTEM MANAJEMEN PEMBELAJARAN ONLINE, MELALUI E-LEARNING - Suryati Suryati (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2018)
One of the impact of the recent development of information and communication technology (ICT), resulted the changes in the learning process such as the possibility the absence of teachers in the classroom. Most of learning process is no longer dependent on the teacher as the only source of learning, and can take place anytime and anywhere, as well as the learning process is no longer just a form of verbal communication between teachers and students. With the rapid development of ICT in education, with the Internet as an integral part in it, resulted many educational institutions including UT (Universitas Terbuka) which offers a web-based learning, or often referred to as online lectures or E-Learning. This type of learning like this of course requires good and optimum management, as well as modify some sort of things, to ensure so that the learning objectives can be achieved.